Compatibility of common IV drugs with 6% hydroxyethyl starch 130/0.42 and 4% gelatin. Issue 2 (9th January 2018) - Heiderich, Sebastian; auf der Springe, Anna; Jürgens, Jonas; Koppert, Wolfgang; Leffler, Andreas; Sümpelmann, Robert; Dennhardt, Nils
Summary: Background: Acetate‐containing colloid infusion solutions are recommended to recover normovolemia during pediatric anesthesia. Until now, no studies investigating the compatibility with common anesthetic drugs were available. Aims: This in vitro study was conducted to reveal possible incompatibilities between common anesthetic drugs and the acetate‐containing colloid infusion solutions 6% hydroxyethyl starch and 4% gelatin with normal saline as control. Methods: The colloid infusion solutions were mixed 1:1 with 29 common intravenous drugs in concentrations used in daily clinical practice. Macroscopically visible changes as well as electrical conductivity, pH, and turbidimetric light diffusion at 405 nm were measured immediately after mixing and subsequently 30 and 60 minutes later. All experiments were conducted in triplicate. Results: Fifty‐nine of the 87 colloid infusion‐drug mixtures showed no significant changes in pH, electrical conductivity, turbidimetrically detectable light diffusion, or macroscopic appearance after mixing with hydroxyethyl starch, gelatin, and NaCl 0.9%. Fifteen mixtures showed equivocal reactions, and 13 mixtures showed incompatibility reactions. Conclusion: Most of the tested drugs did not show observable incompatibility reactions. However, some common drugs are highly incompatible with colloid infusion solutions: gelatin (cefazolin, diazepam, midazolam, phenytoin, vancomycin), hydroxyethyl starch (diazepam, midazolam, phenytoin, thiopental), and NaCl 0.9% (diazepam, ketamine (S), phenytoin, thiopental). These combinations should be avoided in clinical practice in case there are fewer intravenous lines available than needed.